Frequency and classification of oral neoplasms in canine patients at the Small Animal Clinic of the Universidad Nacional Mayor de San Marcos (2009-2013) - Hurtado Y., Rosalyn (2020)
The aim of this study was to determine the frequency of oral neoplasms diagnosed histopathologically in canine patients of the Small Animal Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos (Lima, Peru) in the period of January 2009 till December 2013. The variables age, sex, body weight, breed, anatomical location, and histological classification were considered. Of 238 histopathological reports of canine patients, 192 (80.7%) were neoplasms and 23 (12%) were oral neoplasms. Malignant neoplasms were of greater presentation (73.9%), with oral melanoma being the most frequent (21.7%), and the most frequent benign neoplasm was epulis (17.4%). Males were mostly affected (65.2%). The age group with the greatest presentation of malignancies was between 6 and 10 years (52.2%) and the body weight was between 25 and 44 kg (47.8%). Purebred canines were the most affected (69.6%), especially the Rottweiler and Labrador Retriever (13% each breed). The most common anatomical location was the gingiva (69.6%).